Microstructure and mechanical properties of a 0.1C5Mn3Al steel fabricated by warm drawing. Issue 1 (1st July 2022) - Zhang, L; Cai, P; Cheng, X; Zhang, L; Hou, Z; Huang, X
Abstract: In the present study, a recently developed low density 0.1C5Mn3Al dual phase steel was subjected to warm drawing at 600 °C. Microstructure observations and mechanical properties were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and tensile tests. It was found that carbide precipitates together with laminated ferrite were formed before and after warm drawing. After warm drawing by a Von Mises strain of 1.96, the yield stress (YS) improved from 650 MPa to 1100 MPa and the uniform elongation (UE) dropped to 2%. Further heat treatments were performed to tune the microstructures and mechanical properties. Discontinuous yielding phenomenon was widely observed in the heat treated samples and 15% hot rolling was used to eliminate this discontinuous yielding.